IMPROVING THE SCIENTIFIC AND METHODOLOGICAL BASIS OF DISTANCE TRAINING OF TEACHERS OF FUTURE TECHNOLOGICAL EDUCATION - Kalmuratova Khurliman Arislanbaevna (Scholar Express Journal, 2022)
This article discusses the methods used to improve the scientific and methodological framework for distance learning for future technology education teachers, as well as convenient ways to read, teach and improve their skills online
Keywords: Distance; advanced training; method; internet